Sport Civic Society – Approaches and Facts - Szabados, György; Helmeczi, András; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Dajnoki, Krisztina (International Journal of Engineering and Management Sciences, 2020)
After the change of regime in Hungary in 1989, the domestic civic sphere started to improve, and after numerous change in the legal regulation, currently the Act on Civic Organizations (Act 174/2011.) rules the operation of the sector before all, supplemented by additional legal background. The vital component of the new regulation is possibility of the appearance of the novel organizational form, the civic society, which is quite odd even considering the past and even on international level. The database enabling the statistical overview of the domestic nonprofits publish the end of 2019 provides no information on the data and operational features for this organizational form, which provides a thorough reason for the researcher to be interested in the topic and the organizations. Through the possible secondary data, a primary database of a lately done sports civic organization related research includes such basic data (even its sample height is small), which may be considered as a starting point at the examination of the specifications of the sports related civic societies.